KEBIJAKAN PENGGANTIAN BERDASARKAN OPORTUNITAS UNTUK SISTEM YANG SIKLUS HIDUPNYA PENDEK - Setio Wigati, Slamet
Abstract : The life cycle of the system, which its technology develops fast, tends to be short. The emerging system with better technology often triggers the replacement of the existing system due to technical and economical reason. In this case, the emerging of new system can be perceived as an opportunity to replace the existing system. This research studies replacement policy based on opportunity for short life cycle system. The opportunity comes randomly and it is modeled as a Homogeneous Poisson Process with parameter ?. System failure during and after warranty period is restored by minimal repair. The system is preventively replaced (1) at S if opportunity occurs in t 5 S or (2) at t if opportunity occurs in t > S. During the time between the occurrence of opportunity and the time instant of replacement, the user may incur penalty cost due to the delay of replacement. Decision variable for this policy is S, which describes a minimal operating time of the existing system. Optimal value of S (S*) is attained by minimizing expected cost per replacement period. The conditions of S*, which is fmite and unique are given. Finally some numerical results are also presented to illustrating optimal condition.